The Influence Of Training On The Precision And Accuracy Of Upper Arm Circumference Measurements By Posyandu Cadres - Herlina, Revi; Simbolon, Demsa; Jumiyati, Jumiyati (Jurnal Riset Kesehatan, 2025)
Integrated Healthcare Center cadres are members who come from the community in their area and are willing, able, and have the time to organize Posyandu activities. This study aims to determine the effect of training on knowledge of precision and accuracy of UAC measurements by posyandu cadres. The research design used the pre-experimental with one group pretest-posttest design using a purposive sampling technique, selected by inclusion and exclusion criteria. With a total sample of 24 Posyandu cadres at the Sawah Lebar Health Center. The population in this study were Posyandu cadres at the Sawah Lebar Health Center with a total of 69 cadres. Data were analyzed using the T-test Dependent and Mc. Nemar. Â The results of the Dependent T-test showed that there was a change in the level of knowledge of UAC measurements by Posyandu cadres at the Sawah Lebar Health Center before and after being given training (p-value = 0.0001). The results of the McNemar test for cadres in measuring UAC showed that there was a change in the level of knowledge and skills in measuring UAC before and after training (p-value=0.0001). Suggestions for community health centers are that cadres need to be involved in training activities regarding UAC measurements to increase the precision and accuracy of UAC measurements, periodically regarding the results of UAC measurements carried out by posyandu cadres.